Lidar measurements of polar stratospheric clouds during the 1989 airborne Arctic stratospheric expedition - Ismail, Syed; Browell, Edward V. (1991)
The Airborne Arctic Stratospheric Expedition (AASE) was conducted during January to February 1989 from the Sola Air Station, Norway. As part of this expedition, the NASA Langley Research Center's multiwavelength airborne lidar system was flown on the NASA Ames Research Center's DC-8 aircraft to measure ozone (O3) and aerosol profiles in the region of the polar vortex. The lidar system simultaneously transmitted laser beams at 1064, 603, 311, and 301.5 nm to measure atmospheric scattering, polarization and O3 profiles. Long range flights were made between Stavanger, Norway, and the North Pole, and between 40 deg W and 20 deg E meridians. Eleven flights were made, each flight lasting an average of 10 hours covering about 8000 km. Atmospheric scattering ratios, aerosol polarizations, and aerosol scattering ratio wavelength dependences were derived from the lidar measurements to altitudes above 27 km. The details of the aerosol scattering properties of lidar observations in the IR, VIS, and UV regions are presented along with correlations with the national meteorological Center's temperature profiles.